A Zinc-Mediated Deprotective Annulation Approach to New Polycyclic Heterocycles - Lucia Veltri; Roberta Amuso; Marzia Petrilli; Corrado Cuocci; Maria A. Chiacchio; Paola Vitale; Bartolo Gabriele (Molecules, 2021)
A straightforward approach to new polycyclic heterocycles, 1H-benzo[4,5]imidazo[1,2-c][1,3]oxazin-1-ones, is presented. It is based on the ZnCl2-promoted deprotective 6-endo-dig heterocyclization of N-Boc-2-alkynylbenzimidazoles under mild conditions (CH2Cl2, 40 °C for 3 h). The zinc center plays a dual role, as it promotes Boc deprotection (with formation of the tert-butyl carbocation, which can be trapped by substrates bearing a nucleophilic group) and activates the triple bond toward intramolecular nucleophilic attack by the carbamate group. The structure of representative products has been confirmed by X-ray diffraction analysis.